Empowering PGMI Students in Developing Interactive Mathematics Teaching Materials Based on Digital Books at MIS Al-Jihad Palangka Raya - Afna Nadila; Alif Bismillah; Rismawati Rismawati; Sabariah Sabariah; Zaitun Qamariah; Hadma Yuliani (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Technology development has brought significant changes in education, demanding students' active role as prospective educators to innovate in learning. This article aims to describe the role of Elementary Madrasah Teacher Education (PGMI) students in collaborative community service to develop interactive teaching materials based on digital books in Mathematics subjects in class IV of MIS Al-Jihad Palangka Raya using the ABCD method (Audience, Behaviour, Condition, Degree). The study results showed that the teaching materials developed were feasible (material validation 97%, design 96%), received positive teacher responses (82%), and significantly impacted student learning outcomes. Thus, PGMI students are essential in supporting compelling and engaging digital-based learning innovations.